Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s13205-019-1907-1
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy for the efficient production of pyocyanin, a versatile pigment, in Pseudomonas aeruginosa OG1 via toluene addition

Abstract: Pseudomonas aeruginosa produce pyocyanin, which is an extracellular secondary metabolite and multifunctional pigment. In this study, the effects of several surfactants (Tween 20, Tween 80 and Triton X-100) and organic solvents (toluene and chloroform) on pyocyanin production and cell growth were investigated in submerged culture of P. aeruginosa OG1. Organic solvents were found to be more effective in the production of pyocyanin. The maximum production of pyocyanin (33 mg/L) was achieved when 0.2% toluene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…However, pyocyanin remains a costly reagent (e.g., €118 for 5 mg on Merck website). Therefore, the production of pyocyanin is optimized by many research groups by adjusting process conditions, genetic engineering of the microorganisms, or the addition of various substances to the medium, including nanomaterials (Sismaet et al 2014;El-Fouly et al 2015;Ozdal 2019;Ozdal et al 2019;Bacame-Valenzuela et al 2020;da Silva et al 2021;Elbargisy 2021). The analysis of the literature shows that most of the data concerning the influence of nanomaterials on pyocyanin production indicate the inhibition of pigment production.…”
Section: Introductionmentioning
confidence: 99%
“…However, pyocyanin remains a costly reagent (e.g., €118 for 5 mg on Merck website). Therefore, the production of pyocyanin is optimized by many research groups by adjusting process conditions, genetic engineering of the microorganisms, or the addition of various substances to the medium, including nanomaterials (Sismaet et al 2014;El-Fouly et al 2015;Ozdal 2019;Ozdal et al 2019;Bacame-Valenzuela et al 2020;da Silva et al 2021;Elbargisy 2021). The analysis of the literature shows that most of the data concerning the influence of nanomaterials on pyocyanin production indicate the inhibition of pigment production.…”
Section: Introductionmentioning
confidence: 99%
“…Serratia marcescens MO-1 isolated from grasshopper (Poecilimon tauricola) has both chitinase activity (Okay et al, 2013) and the ability to produce prodigiosin pigment (Kurbanoglu et al, 2015) which has antimicrobial and anticancer properties. Also, Pseudomonas aeruginosa OG1 isolated from cockroaches (Blatta orientalis) can produce pyocyanin, a pigment of biotechnological importance (Ozdal, 2019). Insects can change their ecological and physiological properties thanks to symbiotic bacteria .…”
Section: Resultsmentioning
confidence: 99%
“…The addition of organic solvents seems to be a field where a broader screening is reasonable. It has been reported that an addition of toluene increases the saturated fatty acid content in the bacterial membranes and, thus, leads to increased membrane rigidity [29]. Possibly, an altered membrane composition influenced the secretion of metabolites in C. coralloides.…”
Section: Discovery Of New Secondary Metabolite Mfs After Bivariate Os...mentioning
confidence: 99%